Pressure Relieving Support Surfaces for Pressure Ulcer Prevention (PRESSURE 2): Clinical and Health Economic Results of a Randomised Controlled Trial. (September 2019) - Nixon, Jane; Smith, Isabelle L.; Brown, Sarah; McGinnis, Elizabeth; Vargas-Palacios, Armando; Nelson, E. Andrea; Coleman, Susanne; Collier, Howard; Fernandez, Catherine; Gilberts, Rachael; Henderson, Valerie; Muir, Delia; et al.
Abstract: Background: Pressure ulcers (PUs) are complications of serious acute/chronic illness. Specialist mattresses used for prevention lack high quality effectiveness evidence. We aimed to compare clinical and cost effectiveness of 2 mattress types. Methods: Multicentre, Phase III, open, prospective, parallel group, randomised controlled trial in 42 UK secondary/community in-patient facilities. 2029 high risk (acutely ill, bedfast/chairfast and/or Category 1 PU/pain at PU site) adult in-patients were randomised (1:1, allocation concealment, minimisation with random element) factors including: centre, PU status, facility and consent type. Interventions were alternating pressure mattresses (APMs) or high specification foam (HSF) for maximum treatment phase 60 days. Primary outcome was time to development of new PU Category ≥ 2 from randomisation to 30 day post-treatment follow-up in intention-to treat population. Trial registration: ISRCTN 01151335. Findings: Between August 2013 and November 2016, we randomised 2029 patients (1016 APMs: 1013 HSF) who developed 160(7.9%) PUs. There was insufficient evidence of a difference between groups for time to new PU Category ≥ 2 Fine and Gray Model Hazard Ratio HR = 0.76, 95%CI0.56–1.04); exact P = 0.0890; absolute difference 2%). There was a statistically significant difference in the treatment phase time to event sensitivity analysis, Fine and Gray model HR = 0.66, 95%CI, 0.46–0.93; exact P = 0.0176); 2.6% absolute difference). Economic analyses indicate that APM are cost-effective. There were no safety concerns. Interpretation: In high risk (acutely ill, bedfast/chairfast/Category 1 PU/ pain on a PU site) in-patients, we found insufficient evidence of a difference in time to PU development at 30-day final follow-up, which may be related to a low event rate affecting trial power. APMs conferred a small treatment phase benefit. Patient preference, low PU incidence and small group differences suggests the need for improved targeting of APMs with decision making informed by patient preference/comfort/rehabilitation needs and the presence of potentially modifiable risk factors such as being completely immobile, nutritional deficits, lacking capacity and/or altered skin/Category1 PU.